Race and politics : Asian Americans, Latinos, and whites in a Los Angeles suburb - Saito, Leland T., 1955- (Asian American experience., 1998)
By tracing grass-roots political organization along racial and ethnic lines, Race and Politics focuses on the construction of new identities, especially the panethnic affiliation "Asian American".